Population spatial synchrony enhanced by periodicity and low detuning with environmental forcing. Issue 1903 (29th May 2019) - Haynes, Kyle J.; Walter, Jonathan A.; Liebhold, Andrew M.
Abstract : Explaining why fluctuations in abundances of spatially disjunct populations often are correlated through time is a major goal of population ecologists. We address two hypotheses receiving little to no testing in wild populations: (i) that population cycling facilitates synchronization given weak coupling among populations, and (ii) that the ability of periodic external forces to synchronize oscillating populations is a function of the mismatch in timescales (detuning) between the force and the population. Here, we apply new analytical methods to field survey data on gypsy moth outbreaks. We report that at timescales associated with gypsy moth outbreaks, spatial synchrony increased with population periodicity via phase locking. The extent to which synchrony in temperature and precipitation influenced population synchrony was associated with the degree of mismatch in dominant timescales of oscillation. Our study provides new empirical methods and rare empirical evidence that population cycling and low detuning can promote population spatial synchrony.